2014
DOI: 10.1007/s00417-014-2672-9
|View full text |Cite
|
Sign up to set email alerts
|

Calculating the predicted retinal thickness from spectral domain and time domain optical coherence tomography – comparison of different methods

Abstract: Several methods can be used to convert central retinal thickness values from SD-OCT to the predicted TD-OCT value, or vice versa, with high degrees of accuracy and reliability. These methods may allow comparison of OCT values from SD-OCT and TD-OCT devices in clinical trials and standard patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The study enrolled eyes with BCVA letter scores of 24-78 (approx. Snellen 20/320 to 20/32) and DME involving the foveal center with CRT greater than roughly 325 μm on modern SD-OCT (>250 μm on Zeiss Stratus with gender-specific cutoffs) [80] . The interim results after 1 year showed a mean gain that was +2.1 letters higher for aflibercept 2 mg than for ranibizumab 0.3 mg (the approved dose in the US, 0.5 mg is the approved dose in Europe) ( p = 0.03).…”
Section: Afliberceptmentioning
confidence: 99%
“…The study enrolled eyes with BCVA letter scores of 24-78 (approx. Snellen 20/320 to 20/32) and DME involving the foveal center with CRT greater than roughly 325 μm on modern SD-OCT (>250 μm on Zeiss Stratus with gender-specific cutoffs) [80] . The interim results after 1 year showed a mean gain that was +2.1 letters higher for aflibercept 2 mg than for ranibizumab 0.3 mg (the approved dose in the US, 0.5 mg is the approved dose in Europe) ( p = 0.03).…”
Section: Afliberceptmentioning
confidence: 99%
“…Several studies have reported the results of comparing multiple OCT devices with each other,2729 including methods of converting measurements from one model to those of another 30. In this study, the signal strength did not play a significant role in predicting macular thickness measurements.…”
Section: Discussionmentioning
confidence: 50%
“…The diagnosis of PCV and its differentiation from nAMD was performed using the diagnostic criteria described in the EVEREST and EVER EST II studies [6][7][8][9][10][11][12]. Central subfield retinal thickness (CSFT) was measured using the proprietary Heidelberg viewer software [13][14][15][16][17][18]. Trained graders screened each OCT B-scan for segmentation errors and manually adjusted these when errors were present.…”
Section: Methodsmentioning
confidence: 99%